2016
DOI: 10.1103/physrevb.93.241301
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic moments in a helical edge can make weak correlations seem strong

Abstract: We study the effect of localized magnetic moments on the conductance of a helical edge. Interaction with a local moment is an effective backscattering mechanism for the edge electrons. We evaluate the resulting differential conductance as a function of temperature T and applied bias V for any value of V /T . Backscattering off magnetic moments, combined with the weak repulsion between the edge electrons results in a power-law temperature and voltage dependence of the conductance; the corresponding small positi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 35 publications
(67 reference statements)
4
53
0
Order By: Relevance
“…The question of the effect of magnetic impurities on the conductance along helical edges was the subject of theoretical attention as well, considering different forms of impurities, coupling, and electronic band structures [35][36][37][38][39][40][41][42][43][44][45][46][47]. At low temperatures and in the absence of strong electron-electron interactions, a generic magnetic impurity forms a Kondo singlet and is screened out, allowing the helical edge to reconstitute itself around it and, therefore, has no effect on the conductance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The question of the effect of magnetic impurities on the conductance along helical edges was the subject of theoretical attention as well, considering different forms of impurities, coupling, and electronic band structures [35][36][37][38][39][40][41][42][43][44][45][46][47]. At low temperatures and in the absence of strong electron-electron interactions, a generic magnetic impurity forms a Kondo singlet and is screened out, allowing the helical edge to reconstitute itself around it and, therefore, has no effect on the conductance.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that this can be understood due to the fact that timereversal symmetry allows backscattering only accompanied with a spin-flip of the impurity, which can be further flipped back only with backscattering in the opposite direction, thus prohibiting a steady-state backscattered current. In order to circumvent this limitation while preserving time-reversal symmetry, one has to consider an anisotropic exchange coupling [38,[45][46][47] or describe coupling to a many-level interacting quantum dot [29,40,43].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, even in the absence of time-reversal symmetry breaking, electronelectron interactions may induce backscattering [18], resulting in the suppression of the helical edge conductance at finite temperatures (see [19] and references therein). A combination of electron-electron interactions and magnetic impurities can significantly modify the picture of ideal helical edge transport [20][21][22][23][24].…”
mentioning
confidence: 99%
“…One dimensional (1D) helical edge modes of two-dimensional TIs possess lock-in relation between electron spin and momentum [4,5]. Though this locking may protect transport against disorder [6][7][8], the protection in realistic TIs is not perfectly robust; reasons for this remain an open and intensively debated question [6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%